189k views
5 votes
Look at attachment

**giving BRANIEST to FIRST to answer:)

Look at attachment **giving BRANIEST to FIRST to answer:)-example-1
User Maxhs
by
4.7k points

1 Answer

1 vote

Answer:

x=-7

Explanation:

Let's solve your equation step-by-step.

−2(3x+9)=24

Step 1: Simplify both sides of the equation.

−2(3x+9)=24

(−2)(3x)+(−2)(9)=24(Distribute)

−6x+−18=24

−6x−18=24

Step 2: Add 18 to both sides.

−6x−18+18=24+18

−6x=42

Step 3: Divide both sides by -6.

−6x /−6

= 42 /−6

x=−7

User Nguyen Phuong
by
5.3k points